GAMBARAN KELENGKAPAN PERSETUJUAN TINDAKAN KEDOKTERAN (INFORMED CONSENT) DI RS UNIVERSITAS SUMATERA UTARA - AMINI, RINI SRI (LP2MTBM MAKARIOZ, 2022)
Background: Health service facilities are places where health services are carried out which can be used for medical or dental practice, one of the health service facilities is a hospital. In supporting health services in the form of conveying/providing information about the patient's condition, it is provided by the doctor who carries out medical procedures, whether requested or not requested by the patient. Objective: To describe the completeness of informed consent at North Sumatra University Hospital in March 2018. Method: in this research is descriptive with a qualitative approach. The research design used in this study was cross sectional, namely data on the completeness of approval for medical procedures in the surgical ward in March and the research object was 70 sheets providing information on medical procedures. Meanwhile, the object of this research is a sheet providing information on medical procedures. Data collection using observation, interviews and documentation studies. Results: The patient's right to receive a complete detailed explanation includes: diagnosis and procedures for medical procedures, the purpose of the medical action being carried out, other alternative actions and their risks, risks and complications that may occur, prognosis for the action being carried out. The completeness of filling out the sheet providing information on medical procedures is known to be 100% complete in filling out identification items, 78.57% in complete information giving items, 37.14% in information recipients, 82.1% in alternatives, and 84.2% in doctor authentication and 55.71% in patient authentication. as for factors that influence the completeness of Human Resources